Corner shop in Russia - Jeremy Younkin:::Creator::::::::::::
Taken from room 206 of the Savoy Hotel at corner of Ulica Rozhdestvenska and Ulica Pushechnaya. This is the same perspective from which Capa took a photo that was published in A Russian Journal. The building across street is now a pizzeria. This photographer retraced Steinbeck's and Capa's travels 50 years later. Color.